OP52 Exploring the association between tuberculosis and diabetes in a UK primary care dataset. (13th September 2016) - Pearson, F; Huangfu, P; Pearce, M; McNally, R; Unwin, N; Critchley, JA
Abstract : Background: Many studies have found an increased risk of pulmonary tuberculosis (PTB) amongst those with Diabetes Mellitus (DM), however, evidence on whether the association is specific to disease sub-types or is bi-directional remains sparse. This study assesses rates of TB, PTB and EPTB amongst those with DM, Type 1 DM (T1DM) and Type 2 DM (T2DM) comparative to those without. It also assesses the converse to investigate association bi-directionality. Methods: Retrospective cohort analyses were completed using primary care data from The Health Improvement Network database (2003–2009). Individuals were classified as either exposed to or unexposed to TB, PTB, EPTB, DM, T1DM or T2DM. The incidence rate ratios (IRR) were calculated amongst each exposure group for outcomes of interest (TB, PTB, EPTB or DM, T1DM, T2DM) using negative binomial regression. Results: TB risk was increased amongst individuals with any DM type (IRR 1.50 (95% CI 1.27–1.76) p < 0.001), T1DM (IRR 1.46 (95% CI 1.10–1.92) P-value = 0.008) and T2DM (IRR 1.54 (95% CI 1.30–1.82) p < 0.001) compared to those without DM. The risk of EPTB amongst those with T1DM was also increased (IRR 2.09 (95% CI 1.19–3.66), p < 0.010). DM risk was increased amongst those who have had TB (IRR 5.65 (95% CI 5.19–6.16) p < 0.001), PTB (IRR 5.74 (95% CI 5.08–6.50) p < 0.001) and EPTB (IRR 4.66 (95% CI 3.94–5.51) p < 0.001) comparative to those without. The risk of T1DM was increased amongst those who have had TB (any sub-type) (IRR 5.49 (95% CI 5.02–6.02) p < 0.001) or EPTB (IRR 0.84 (95% CI 0.35–2.03) p < 0.001) compared to those without. The risk of T2DM was increased amongst those who have had TB (any sub-type) (IRR 2.21 (95% CI 1.68–2.91) p < 0.001), PTB (IRR 5.38 (95% CI 4.73–6.12) p < 0.001) and EPTB (IRR 4.36 (95% CI 3.65–5.22) p < 0.001) compared to those without. Discussion: Within a UK setting, TB risk was increased in those with DM as is DM risk amongst those who have had TB. We are not aware of other studies with sufficient power to assess the risk of DM among those with prior TB. Consideration of the specificity and directionality of these associations will be important in improving TB control and treatment as DM prevalence rises globally. Given the associations identified, it is likely the numbers of individuals suffering from co-morbid disease will burgeon with a need for heightened clinical attention to improve both diabetes control and TB outcomes.